Evaluation of the Economic Profitability of Using Renewable Energy Sources in Agro-Industrial Companies - Denis Syromyatnikov; Varvara Druzyanova; Aleksandr Beloglazov; Alexander Bakshtanin; Tatiana Matveeva (International Journal of Renewable Energy Development, 2021)
The study of the impact of the availability of renewable energy sources (RES) on the competitiveness and cost reduction opportunities is an actual objective for agro-industrial enterprises in the present time. The purpose of this paper was to develop a methodological approach based on a questionnaire survey, an integrated indicator of enterprise competitiveness, a model for assessing energy conservation costs, and regression analysis combined with a hierarchical synthesis of 20 Russian agro-industrial companies. The solution of the problem of nonlinear optimization of agro-industrial companies made it possible to determine the excess of the competitiveness criterion over the criterion of energy conservation cost reduction as a result of the use of RES. The conducted regression analysis showed a close relationship between the competitiveness of the companies under study and the availability of RES. Modeling and hierarchical synthesis of the study results confirmed that the use of RES in the activities of agro-industrial companies stimulates their competitive potential reflected by the competitiveness index and minimizes energy conservation costs. It was also found that there is an inverse regression relationship with a high degree of correlation between the provision of RES and the cost of energy-saving measures. Hence, it can be argued that a greater emphasis on the provision of Russian agro-industrial enterprises with RES can lead to their more sustainable and efficient development due to increased competitiveness and better cost reduction strategies.